The personalization of care services and the early impact on staff activity patterns. (March 2013) - Jacobs, Sally; Abell, Jessica; Stevens, Martin; Wilberforce, Mark; Challis, David; Manthorpe, Jill; Fernandez, Jose-Luis; Glendinning, Caroline; Jones, Karen; Knapp, Martin; Moran, Nicola; Netten, Ann
Summary : This study examines the early impact on care coordinators' (care managers') work activity patterns of implementing the current personalization agenda within English local authorities. The Individual Budget (IB) pilots operated between 2005 and 2007 and provided a basis for personalization that, ultimately, sought to give personal care budgets to every eligible service user in England. Of particular interest was how the pilots impacted upon the roles, responsibilities and activity of care coordinators, who are expected to play a key role in this transformation of social care. A self-administered diary schedule was completed by 249 care coordinators, including teams directly involved in delivering IBs and a comparative sample of teams not involved in the pilots. These data were supplemented by semi-structured interviews with 48 care coordinators and 43 team managers. Findings : The study found that on most measures there were no differences in working patterns between care managers with and without IB holders on their caseload. However, the results do show that – contrary to expectations – more time was spent assessing needs, and that more time generally was required to conduct support planning activities. Application : The findings are necessarily dependent upon the early experiences of the pilot phase of IBs. As personal budgets are rolled out across all eligible service users, it will be interesting to examine whether the time-use of frontline staff, and indeed the wider organization, structure and function of local authority frontline teams, changes further.